Bonded porcelain Inlays and Onlays - F. Farshchian (Tehran University of Medical Sciences, 1992)
Currently, the application and use of porcelain inlays and onlays for anterior and posterior teeth that are made in laboratory is increasing. Present article is aimed to evaluate 1. Advantages of porcelain include their aesthetic, strength, low chair-side, biocompatibility and do not depending on metals 2. Disadvantages of porcelains are undesirable tooth wearing, high cost, needing an expert technician and tooth sensitivity that can lead to endodontic treatments. 3. Methods and materials of working with porcelains are thoroughly discussed in this section.